Implementasi Mata Pelajaran Akidah Akhlak dalam Pembentukan Karakter Siswa Madrasah Ibtidaiyah Miftakhul Falah Kedu Temanggung - Lubna Handayani (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
Character education is understood as an effort to instill intelligence in thinking, appreciation in the form of attitudes, and experience in the form of behavior that is in accordance with the noble values ​​that become one's identity. Character education that is instilled in Islamic education is the creation of the nature of students who have good morals. The importance of character education is because part of the current generation's problems is a moral crisis. The research method used in qualitative research with field research uses a descriptive approach. Based on data analysis, it was found that the form of character education material in learning the moral creed at MI Miftakhul Falah requires teaching, exemplary, and reflection on morals, worship, and aqidah. The most important point in character education is teaching children to behave according to the guidance of the Koran and Sunnah. The implementation of character education in teaching moral principles at MI Miftakhul Falah is carried out in three ways, namely in-class learning activities, outside-class activities and outside-school activities. Existing facilities and infrastructure, admittedly or not, have contributed to facilitating character education in teaching moral principles with existing materials and using habituation, exemplary, and reflection methods as well as methods that activate students in the learning process.